The TikTok Effect: Exploring Gender Norms, Lifestyle, and Cultural Shifts among Gen Z - Sair, Abdus; Aribowo, Aribowo; Kusman, Airlangga Pribadi; Suyatno Ladiqi (Universitas Negeri Surabaya, 2025)
The rise of TikTok as one of the most popular social media platforms and its significant influence on Gen Z has attracted the attention of many parties. However, the impact of TikTok on gender norms, lifestyles, and cultural shifts among Generation Z is still limited, especially in a local context. This article, on the other hand, will explore these issues within the context of East Java. As an exploratory study, this research employs a qualitative approach, involving 20 female students (Gen Z) as participants. Data were collected through unstructured group interviews in four cities in East Java (Surabaya, Malang, Jember, and Mojokerto) and focus group discussions (FGD). The results of this study indicate that TikTok, on one hand, still reinforces conventional gender norms, particularly through video content focused on beauty. However, in terms of lifestyle, TikTok has become a mirror for many members of Generation Z, the majority of whom adhere to Islamic teachings, even among millennial religious figures. TikTok significantly influences Generation Z's lifestyle preferences and acts as a medium for cultural change. It serves as a social and cultural agent, impacting individuals and broader social structures.